Analisis Pendekatan Kolaboratif pada Integrasi Pembelajaran Agama Kristen (PAK) dan Proyek Penguatan Profil Pelajar Pancasila (P5) di SMK Kesehatan Reformasi Pontianak - Rosnamita; Ruben Nesimnasi; Merdiati Marbun (PT. Penerbit Tiga Mutiara, 2024)
This research aimed to identify the implementation, optimization, empowerment of technology, to evaluation of the implementation of the integration of Christian Religious Education Learning (PAK) and the Pancasila Student Profile Strengthening Project (P5) in the formation of student character at SMK Kesehatan Reformasi Pontianak. The method in this study is qualitative with a descriptive approach. The results of the study indicate that the implementation of the integration of PAK and P5 that meets students' needs in fulfilling knowledge of divinity and nationality are Worship Together and Reading the Bible, celebrating the Independence Day of the Republic of Indonesia and the Anniversary of Pontianak City, carrying out independent assignments with the substance of divinity and nationality values, holding a Clean Friday agenda, carrying out presentation and group discussion agendas, and implementing a three-dimensional wall magazine and poster making agenda. In addition, the aspect of technology empowerment needs to be optimized in various moments including the creation of digital-based posters and wall magazines as a representation of the agenda that describes the implementation of digitalization elements holistically, and the evaluation of the effectiveness of the integration of PAK and P5 learning in general is not carried out on a scheduled and regular basis, however, intensive communication and coordination between P5 and PAK teachers in order to integrate divinity and national values ​​are carried out, including together with school management.